STOP TALKING! Inhibition of Speech is Affected by Word Frequency and Dysfunctional Impulsivity - Van Den Wildenberg, Wery; Christoffels, Ingrid (Frontiers in Psychology, 2010)
Speaking is a complex natural behavior that most people master very well. Nevertheless, systematic investigation of the factors that affect adaptive control over speech production is relatively scarce. The present experiments quantified and compared inhibitory control over manual and verbal responses using the stop-signal paradigm. In tasks with only two response alternatives, verbal expressions were slower than manual responses, but the stopping latencies of hand and verbal actions were comparable. When engaged in a standard picture-naming task using a large set of pictures, verbal stopping latencies were considerably prolonged. Interestingly, stopping was slower for naming words that are less frequently used compared to words that are used more frequently. These results indicate that adaptive action control over speech production is affected by lexical processing. This notion is compatible with current theories on speech self-monitoring. Finally, stopping latencies varied with individual differences in impulsivity, indicating that specifically dysfunctional impulsivity, and not functional impulsivity, is associated with slower verbal stopping.